Upaya Meningkatkan Hasil Belajar IPS melalui Model Pembelajaran Discovery Learning pada Siswa Kelas V SD - Arkan Naupal, Azza; Dina Kurnia; Rastinah; Annisa Rahim; Deddy Firduansyah (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to determine the effectiveness of the Discovery Learning model in improving students' learning outcomes in Social Studies, particularly the topic "Indonesiaku Kaya Alamnya" (Indonesia's Natural Wealth), in Grade V of SD Negeri 1 Lesung Batu. The research employed a classroom action research (CAR) method conducted in two cycles. The results showed that in the pre-test of Cycle I, the average student score was 63.57, with only 32% achieving mastery. After implementing the Discovery Learning model, the post-test score in Cycle I increased to an average of 68.21, with 61% of students reaching mastery. A more significant improvement occurred in Cycle II, with a pre-test average of 72.86 and 82% mastery, and a post-test average of 71.25 with 93% of students achieving mastery. These findings demonstrate that the Discovery Learning model is effective in enhancing student learning outcomes and also contributes positively to student engagement and motivation. Thus, the conclusion of this study is that this model is suitable to be applied as an alternative learning model to improve the quality of the social studies teaching and learning process in elementary schools. Keywords: Classroom Action Research, Discovery Learning, Elementary School, Learning Outcomes, Social Studies.